2006
DOI: 10.4269/ajtmh.2006.75.904
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Immunologic Predictors of Efficacy of Treatment or Reinfection Risk for Schistosoma Mansoni

Abstract: Abstract. Most Schistosoma mansoni infections are egg-negative after a single dose of oxamniquine. A cohort of 661 infected children was treated at 6-month intervals and assessed for nutritional and parasitological status. Initial biochemical and immunologic markers were measured in a subset of 84 children. All were treated at the start of therapy and at 6 months. Immunoglobulins only served as markers for active infection. No markers were predictive of cure or reinfection, except initial infection intensity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
(29 reference statements)
1
3
0
3
Order By: Relevance
“…e mean total cholesterol level was significantly (P < 0.05) dropped in the S. mansoni-infected subject as compared with the control group in the current study. is finding is supported by a study from Brazil, which reported a mean total cholesterol level of 123.90 ± 21.52 and 156.31 ± 41.50 for the S. mansoni-positive group and the control group, respectively [41]. e possible cause for reduction of blood total cholesterol in infected hosts might be due to abnormalities in lipid metabolism, and since Schistosoma did not synthesize cholesterol de novo, it is completely dependent on the host cholesterol and fatty acids [42].…”
Section: Discussionsupporting
confidence: 68%
“…e mean total cholesterol level was significantly (P < 0.05) dropped in the S. mansoni-infected subject as compared with the control group in the current study. is finding is supported by a study from Brazil, which reported a mean total cholesterol level of 123.90 ± 21.52 and 156.31 ± 41.50 for the S. mansoni-positive group and the control group, respectively [41]. e possible cause for reduction of blood total cholesterol in infected hosts might be due to abnormalities in lipid metabolism, and since Schistosoma did not synthesize cholesterol de novo, it is completely dependent on the host cholesterol and fatty acids [42].…”
Section: Discussionsupporting
confidence: 68%
“…An interesting finding was a negative standardized mean difference observed in the association between IgE levels and reinfection with schistosomes (Figure 5 and Figure S2) inferred from meta-analysis on 8 studies [23], [31], [39], [44], [48][51]. However, subgroup analyses of these associations with IgE levels against adult worm antigen (SWA) (Figure 5A) and egg antigen (SEA) (Figure 5B) were not statistically significant (For anti-SWA IgE, SMD = −0.06, 95% CI = −0.59–0.46, Z = 0.23, p  = 0.82; for anti-SEA IgE, SMD = −0.03, 95% CI = −0.38–0.32, Z = 0.15, p  = 0.88).…”
Section: Resultsmentioning
confidence: 93%
“…Praziquantel, the current drug of choice for the treatment of schistosomiasis, including cutaneous schistosomiasis, is associated with an overall cure rate of 60–90% in individuals living in endemic areas and approximates 100% in nonendemic areas 30–32 . The subcurative response of patients from disease‐endemic areas is attributed to a high pre‐treatment parasite burden, high re‐infection rates, the circulation of immature parasitic forms that are unaffected by the drugs, drug resistance and noncompliance 30,32,33 .…”
Section: Discussionmentioning
confidence: 99%